Dynamics of incompatibility of quantum measurements in open systems - Addis C; Heinosaari T; Kiukas J; Laine EM; Maniscalco S (AMER PHYSICAL SOC, 2022)
The nonclassical nature of quantum states, often illustrated using entanglement measures or quantum discord, constitutes a resource for quantum information protocols. However, the nonclassicality of a quantum system cannot be seen as a property of the state alone, as the set of available measurements used to extract information on the system is typically restricted. In this work we study how the nonclassicality of quantum measurements, quantified via their incompatibility, is influenced by quantum noise and how a non-Markovian environment can be useful for maintaining the measurement resources.